Identifying factors affecting the effectiveness of physical rehabilitation for individuals with lower leg amputations - Semenova, S.A.; Korolkov, A.N.; Reznikov, V.A.; Lunev, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the factors affecting the effectiveness of physical rehabilitation of individuals with lower leg amputation during the preparation stage for prosthetics and to identify the contribution of individual factors to the recovery process. Methods and structure of the study. The study involved 54 people undergoing rehabilitation treatment after amputation of the lower leg aged from 23 to 60 years. All the subjects received the same set of restorative measures. Results and conclusions. Subjective scales are mainly used to assess the condition of patients. The parameters of anxiety and depression make the greatest contribution to the recovery process. Moreover, by the end of treatment, the level of anxiety decreases, while the level of depression remains at a fairly high level, which subsequently reduces the motivational component and increases problems with further prosthetics. The conducted research revealed the need to develop quantitative criteria and standardized diagnostic methods, which indicates the need to introduce objective scales both to improve the assessment of the condition of the stump and to assess the entire musculoskeletal system, which will allow individualizing rehabilitation programs and reducing the possibility of errors, including when using modern technologies.